Pemanfaatan Fly Ash dan Bottom Ash PLTU Rembang Untuk Pembuatan Beton Menggunakan Semen PPC - Wardhani, Kinan Wintang; Pangestuti, Endah Kanti; Kusumawardani, Rini; Firdaus, Muh Arief (Politeknik Pekerjaan Umum, 2024)
The research aims to reduce the amount of coal burning waste of fly ash and bottom ash PLTU Rembang as a substitution of cement and sand in the production of quality concrete K-225 and waterproof using Portland Pozzolan cement. The method was experimented in the laboratory by making 50 samples of 15 x 15 x 15 cm3 test objects for 28 days, 60 days, and water absorption tests. The test objecte was made in 5 variations: normal concrete (without substitution) and 20% bottom ash substitution concrete and fly ash mixture 0%, 5%, 10%, 15%. Strong K-225 pressure occurs at the age of 60 days on bottom ash substituted concrete 20% with fly ash 0%, 5% 10% and 15% respectively of 245 kg/cm2, 254,67 kg/cm2, 250,67 kg/cm2, dan 250,67 kg/cm2. Water absorption of concrete at 28 days of ashes substitution was less than 20% and ashes flew below 0% and 5%, 10% 15% resulted in 4.85%, 5.17%, 5.05%, and 5.18%. The results of the research showed that the concrete made meets the K-225 quality and better absorption than normal concrete.